G protein-coupled receptor-biased signaling: potential drug discovery to facilitate treatment of metabolic diseases - Shengnan Shen; Qiwen Liao; Liwei Gu; Yongping Zhu; Yanqing Liu; Xinwei Zhang; Junzhe Zhang; Qiaoli Shi; Yuxiang Sun; Jigang Wang; Ligen Lin (Acta Materia Medica)
G protein-coupled receptors (GPCRs) are important, potential drug targets for the treatment of metabolic disorders, such as obesity. GPCRs crosstalk with several transducers, including heterotrimeric G proteins, GPCR kinases (GRKs), and β-arrestins. GPCR-biased agonism has raised the potential of novel drug development to preferentially activate therapeutic signaling pathways over pathways that lead to unwanted side effects. The obesity epidemic and its metabolic complications continue to be a major global public health threat but effective treatments are limited. The accelerated development of structural techniques, like X-ray crystallography and cryo-electron microscopy, has paved the way to understanding how biased agonism measured at GPCRs results in specific downstream physiologic responses. Herein some well-validated GPCR targets are briefly summarized and several new and promising receptors for obesity treatment are outlined. This review highlights the significance of deciphering the role of GPCRs in obesity pathology and biased signaling for drug development. We anticipate the review will facilitate the development of novel GPCR-targeted anti-obesity drugs that lead to heightened therapeutic efficacy with decreased side effect profiles.